A Survey of Accounting Ideas–With on Approach Based On 'Claims To Services' (Book). - Sprouse, Robert T.; Zeff, Stephen A. (The Accounting Review, 1964)
Reviews the book "A Survey of Accounting Ideas–With on Approach Based On 'Claims To Services'," by G. D. Roy.